Устойчивость разностных дробно-рациональных систем - Хусаинов, Д.Я.; Шевеленко, Е.Е. (Український математичний журнал, 1999)
Для систем різницевих рівнянь з дробово-раціональними функціями в правій частині, які записані в уніфікованому векторно-матричиому вигляді, за допомогою другого методу Ляпунова отримано умови стійкості та обчислено розмір радіуса кулі області асимптотичної стійкості. For systems of difference equations with rational functions on the right-hand sides represented in a unified vector matrix form, we obtain stability conditions and calculate a value of the radius of a disk for the domain of asymptotic stability on the basis of the second Lyapunov method.